ON SOFT CONTRA rgb-CONTINUOUS FUNCTION AND SOFT ALMOST rgb-CONTINUOUS FUNCTION IN SOFT TOPOLOGICAL SPACES - Indirani, K. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
The purpose of this paper is to introduce the concept of soft contra-continuity, soft contra rgb-continuity, soft almost continuity and soft almost rgb-continuity in soft topological spaces and some of their properties are also obtained. The relation of these mappings with other soft contra-continuous functions is also introduced. Key words: Soft Set, Soft Topology, Soft rgb-Closed Set, Soft rgb-open set, Soft Contra-continuity, Soft Contra rgb-Continuity, Soft Almost Continuity, Soft Almost rgb-Continuity